2017
DOI: 10.1002/2016ja023536
|View full text |Cite
|
Sign up to set email alerts
|

“Zipper‐like” periodic magnetosonic waves: Van Allen Probes, THEMIS, and magnetospheric multiscale observations

Abstract: An interesting form of “zipper‐like” magnetosonic waves consisting of two bands of interleaved periodic rising‐tone spectra was newly observed by the Van Allen Probes, the Time History of Events and Macroscale Interactions during Substorms (THEMIS), and the Magnetospheric Multiscale (MMS) missions. The two discrete bands are distinct in frequency and intensity; however, they maintain the same periodicity which varies in space and time, suggesting that they possibly originate from one single source intrinsicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…further investigated high-resolution Cluster Wideband Data for all 17 events where these were available, and they revealed the presence of a harmonic line structure in all of them. The emissions may occasionally consist of two frequency bands of interleaved QP elements (Li et al, 2017) and were also observed at altitudes as low as 700 km .…”
Section: 1029/2018ja025382mentioning
confidence: 97%
“…further investigated high-resolution Cluster Wideband Data for all 17 events where these were available, and they revealed the presence of a harmonic line structure in all of them. The emissions may occasionally consist of two frequency bands of interleaved QP elements (Li et al, 2017) and were also observed at altitudes as low as 700 km .…”
Section: 1029/2018ja025382mentioning
confidence: 97%
“…Besides, radial and azimuthal propagation, combined with wave trapping by density gradients, may account for the origin of some of the wave occurrence inside the plasmapause, which otherwise could not be explained by the local excitation mechanism (Ma, Li, Chen, Thorne, & Angelopoulos, 2014;Ma, Li, Chen, Thorne, Kletzing, et al, 2014). In addition, recent observations show a short-timescale (∼minute) quasi-periodicity of wave amplitude with a frequencytime dispersion (similar to chorus chirps) (Boardsen et al, 2014;Fu, Cao, et al, 2014;Li et al, 2017;Němec, Santolík, Hrbáčková, Pickett, & Cornilleau-Wehrlin, 2015;Walker et al, 2016), whose cause is still unclear. Fast magnetosonic waves can interact with the local radiation belt electron population resonantly and nonresonantly, efficiently accelerating some particles to high energies while scattering others into the loss cone (e.g., Albert et al, 2016;Artemyev et al, 2015;Bortnik et al, 2015;Chen et al, 2015;Horne et al, 2007;Li et al, 2014Li et al, , 2015Li et al, , 2016Maldonado et al, 2016;Ma et al, 2016;Mourenas et al, 2013;Ni et al, 2017;Shprits, 2016;Shprits et al, 2013;Tao & Li, 2016;Yang et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…Triggered by the ring distribution of energetic protons, MS waves are initially excited with very oblique wave normal angles and then propagate in both radial and azimuthal directions that are nearly perpendicular to the background magnetic field (e.g., Chen et al, 2011;. Recent observations also reported that, besides the frequently present harmonic structures (e.g., Balikhin et al, 2015), MS waves occasionally consist of discrete wave elements with the rising tone (e.g., Boardsen et al, 2014;Fu et al, 2014) and "zipper-like" periodic structures (Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%